The maternal and fetal outcome of repeat previous one caesarean section - Jain, Uma; Jain, Deepali; Sengar, Shaily; Gupta, Preeti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: The rates of adverse maternal and neonatal outcomes have increased significantly in the last decade. Patients with repeated caesarean deliveries also have a greater risk of placenta previa, placenta accrete, uterine rupture, bowel and bladder injury, and unplanned hysterectomy. Methods: This retrospective study was performed between 01 April 2017 to 31 March 2021, at a private hospital to know about the surgical difficulties and maternal and neonatal complications encountered in cases of repeated LSCS. The outcome of 1028 women admitted with a history of previous LSCS was studied. Results: The 613 patients were given a trial of labour. 40.07% of patients delivered normally. The most common indication for repeat LSCS was CPD in 20.94% and fetal distress 20.12%. The most common complication observed was adhesion in 37.65%. Scar dehiscence in 8.92 %, scar rupture in 0.64%, uterine atony in 4.8%, placenta previa in 3.57%, placenta accrete in 0.64%, injury to the bladder was seen in 0.97%, caesarean hysterectomy was done in only 2 cases and gaped wound was found in 1.13% of cases. 19.15% of neonates were admitted to NICU. Apgar score <7 at 5 minutes in 14.77%. premature neonates were 8.44% RDS was found in 7.62%, birth asphyxia was found in 2.92% cases and neonatal sepsis was found in 1.13%. Conclusions: The dramatic increase in caesarean section rates over the past three decades has been associated with a corresponding increase in maternal morbidity but there a continuous decrease in neonatal morbidity and mortality rates because of advances in neonatal medicine.